A NEW DIALETICS CENTRE/PERIPHERY: CONSUMPTION PATTERNS AND PRACTICES IN THE SUBURBAN AREAS - Cirelli, Caterina; Graziano, Teresa; Mercatanti, Leonardo; Nicosia, Enrico; Porto, Carmelo Maria (Revista Cidades, 2021)
This paper deals with the analysis of current changes which have been recently shaping unprecedented urban structures in some suburban areas, due to the emerging of new consumptions spaces. In particular, the work aims at highlighting the effect of urban sprawl on the main Sicilian metropolitan areas, also moulded by the diffusion of the suburban retailing formats, in order to evaluate to what extent these dynamics have been contributing to the configuration of new urban landscapes and unprecedented socio-economic structures, not to mention the new consumption spacessupport in the process of containing social and economic marginalisation.